2022
DOI: 10.3389/fendo.2022.891217
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sex Hormones and Sex Hormone-Binding Globulin Levels With Bone Mineral Density in Adolescents Aged 12–19 Years

Abstract: BackgroundSex hormones are recognized to play a significant role in increasing bone mineral density (BMD) and promoting bone maturation during adolescence. The purpose of our study was to use a database with large population data to evaluate the association of BMD with sex hormones (including testosterone and estradiol) and sex hormone-binding globulin (SHBG) in adolescent boys and girls aged 12–19 years.MethodsThe data for our study were taken from the National Health and Nutrition Examination Survey 2013-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Several studies have shown that sex, smoking, diet, and physical activity are strong determinants of adolescent BMD. In the present study, however, there was no evidence of interaction between THM exposure and physical activity, milk product consumption, and smoking status, suggesting that the effects of THM exposure are independent of these known risk factors. Interestingly, the association of blood Cl-THM concentrations and TBLH BMD z -scores was modified by weight and obesity.…”
Section: Discussioncontrasting
confidence: 69%
“…Several studies have shown that sex, smoking, diet, and physical activity are strong determinants of adolescent BMD. In the present study, however, there was no evidence of interaction between THM exposure and physical activity, milk product consumption, and smoking status, suggesting that the effects of THM exposure are independent of these known risk factors. Interestingly, the association of blood Cl-THM concentrations and TBLH BMD z -scores was modified by weight and obesity.…”
Section: Discussioncontrasting
confidence: 69%
“…In contrast, a mercury exposure experiment in Girella punctata found that short-term mercury exposure reduced osteoclast activity and may be involved in the protection of osteoblasts (Yachiguchi et al, 2014). As is well known, estrogen de ciency is associated with increased risk of osteoporosis and decreased bone mineral density (Xu et al, 2022;Zhu et al, 2021;Riggs, 2000). Previous studies have found that mercuric chloride can exert estrogen-like effects to regulate the activity of osteoblasts (Suzuki et al, 2004;Wang et al, 2005;Jin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ke Xu et al investigated the relationship between gender hormones with BMD value. They demonstrated that the relationship between sex hormones such as testosterone, estradiol, or sex hormone-binding globulin levels and BMD were opposite in the boy and girl subgroups 28 . In summary, sex hormones might be the crucial cause of this association.…”
Section: Discussionmentioning
confidence: 99%